Improvement of Inspirational Story Writing Skills with a Savi Approach (Somatic, Auditory, Visual, Intellectual) in Grade IX Students of State Junior High School 1 Paliyan, Gunungkidul Regency - Warra Mahardhika; Esti Swastikasari (International Journal of Multilingual Education and Applied Linguistics, 2025)
This study aims to improve the inspirational story writing skills of ninth grade students at SMP Negeri 1 Paliyan, Gunungkidul Regency, through the SAVI (Somatic, Auditory, Visual, Intellectual) approach. The background of this research is the students’ low ability to express ideas coherently, meaningfully, and attractively in the form of inspirational stories. The SAVI approach is expected to make the learning process more enjoyable, active, and meaningful by involving various student learning styles. This research employs a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the research were 32 ninth-grade students. Data were collected through observation, interviews, documentation, and writing skill tests. The data were analyzed using both qualitative and quantitative descriptive methods to assess the improvement in students’ writing skills. The results of the study indicate that the SAVI approach effectively enhances students’ inspirational story writing skills. In the first cycle, students showed initial improvements, though they had not yet reached the success criteria. After revisions in the second cycle, students' writing skills significantly improved and met the expected indicators. The improvements were evident in aspects such as text structure, language use, and idea development. Therefore, the SAVI approach is effective in teaching inspirational story writing.